Characteristics, outcomes, and predictors of de novo malignancy after heart transplantation - Youn, Jong-Chan; Kim, Darae; Kim, In-Cheol; Lee, Hye Sun; Choi, Jin-Oh; Jeon, Eun-Seok; Nishihara, Keith; Kransdorf, Evan P.; Chang, David H.; Kittleson, Michelle M.; Patel, Jignesh K.; Ramzy, Danny; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background Post-transplant malignancy (PTM) causes long-term morbidity and mortality in heart transplant (HTx) recipients. However, the detailed characteristics or predictors of PTM are not well-known. We evaluated the incidence, characteristics, long-term outcomes, and predictors of de novo PTM using a single center large-volume database. Methods We retrospectively analyzed the types and characteristics of de novo PTM in 989 patients who underwent HTx. Univariate and multivariate logistic regression analyses were used for the PTM prediction model. Results Two hundred and six patients (20.8%) had de novo PTMs (241 cancers) during a median follow-up of 11.5 years. PTM patients were older than non-PTM patients, received immunosuppressive therapy for a longer period, and were more likely to be male and white. Skin cancers were the most frequent types of malignancy (60.6%) followed by prostate (9.5%), lung (7.1%), and breast (4.1%) cancers. Although most cancers (88.8%) were surgically resected at initial presentation, about half (47.3%) recurred or progressed. Patients with skin cancer and non-skin cancer had significantly lower overall survival (P < 0.001) than patients without cancer. Older age (P < 0.001), white race (P = 0.001), and longer time receiving immunosuppressive therapy (P < 0.001) were independent predictors for PTM. Conclusion Older age, white race, and longer administration of immunosuppressive therapies were independent risk factors for PTM, which was associated with increased mortality. Further research is necessary for the prevention and early detection of PTM in HTx recipients.